Personality, Subjective Well-Being, and the Serotonin 1a Receptor Gene in Common Marmosets (Callithrix jacchus) - Weiss, Alexander; Yokoyama, Chihiro; Hayashi, Takuya; Inoue-Murayama, Miho (bioRxiv, 2021)
Studies of personality traits in common marmosets (Callithrix jacchus) indicate that there are five or six constructs---sociability, dominance, neuroticism, openness, and two related to conscientiousness---that define personality in common marmosets. The present study attempted to determine whether our earlier study of laboratory-housed individuals only yielded three domains---Dominance, Sociability, and Neuroticism---because of a low amount of between-subjects variance. We therefore increased our sample size from 77 to 128. In addition, we ascertained the reliability and validity of ratings and whether polymorphisms related to the serotonin 1a receptor were associated with personality. We found Sociability, Dominance, and Negative Affect factors that resembled three domains found in previous studies, including ours. We also found an Openness and Impulsiveness factor, the latter of which bore some resemblance to Conscientiousness, and two higher-order factors, Pro-sociality and Boldness. Further analyses could not exclude the possibility that Pro-sociality and Boldness represented a higher-level of personality organization. Correlations between personality factors and well-being were consistent with the definitions of the factors. There were no significant associations between personality and genotype. These results are consistent with the possibility that common marmoset personality structure varies as a function of rearing or housing variables that have not yet been investigated systematically. Competing Interest Statement The authors have declared no competing interest. Footnotes * In response to reviewer comments, we changed the figure into a table, which should be a clearer summary of the past literature. There were also other minor edits, such as a revised abstract and some edits for clarity. The author affiliations were changed a bit, namely the order of affiliations for AW were changed and one affiliation for MI-M was deleted.